Dental age in children with impacted maxillary canines. (19th May 2021) - Lövgren, Mai Lin; Ransjö, Maria; Uribe, Pamela; Westerlund, Anna
Abstract: Objective: The aim of this study was to evaluate if delayed dental development is a cause of postponed care for patients with impacted maxillary canine (IMC). Materials and methods: This case-control study was based on 403, 355 children and adolescents in Region Västra Götaland, Sweden. The subjects, who were in the age range of 9–16 years during the period of 2011–2013, underwent surgical exposure or removal of a maxillary canine. Demirjian's dental age assessment was carried out on panoramic radiographs. Results: In total, 1028 patients, 514 with IMC and 514 age- and gender-matched controls, were enrolled. The patients with IMC exhibited a dental development delay of 0.2 years compared to the control group. In the impaction sub-groups, the female patients, patients in the chronological age group of 12–13 years, and patients with palatally positioned IMC had a significantly lower dental age than their paired-control subjects. Conclusions: Overall, the difference in dental age between patients with or without IMC is significant but small, and as such is likely of minor clinical relevance. Therefore, the timing of preventive care and treatment for patients with IMC should be the same as that for patients with normally erupting canines.